Beyond Agencys Limits: Street Childrens Mobilities in Southern Ghana - Ungruhe,Christian (2019)
As a response to widespread conceptualizations of street childhood in the global South as a state of misery and marginalization, recent studies tend to portray street children as social agents. However, many refer to tactical or thin agency in order to point out the limited scope of those young peoples practices. Yet, the problem of acknowledging a lower degree of agency is that it separates children and youth living in environments outside the norm from those who stay with their parents and attend school. This constellation is particularly inadequate in the realm of street childhood in the global South, as it constructs fixed entities of different life worlds that are indeed fluid since street children frequently move between the various domains of socialization. I propose that the social, spatial and temporal mobilities of street children can best be explored through childrens biographical life stories, focusing here on street children in southern Ghana.